A B‐type histone acetyltransferase Hat1 regulates secondary metabolism, conidiation, and cell wall integrity in the taxol‐producing fungus Pestalotiopsis microspora. (11th July 2016) - Zhang, Qian; Chen, Longfei; Yu, Xi; Liu, Heng; Akhberdi, Oren; Pan, Jiao; Zhu, Xudong
Abstract : In filamentous fungi, many gene clusters for the biosynthesis of secondary metabolites often stay silent under laboratory culture conditions because of the absence of communication with its natural environment. Epigenetic processes have been demonstrated to be critical in the expression of the genes or gene clusters. Here, we report the identification of a B‐type histone acetyltransferase, Hat1, and demonstrate its significant roles in secondary metabolism, conidiation, and the cell wall integrity in the fungus Pestalotiopsis microspora . An hat1 deletion strain shows a dramatic decrease of SMs in this fungus, suggesting hat1 functions as a global regulator on secondary metabolism. Moreover, the mutant strain hat1Δ delays to produce conidia with significantly decreased number of conidia, while shows little effect on vegetative growth, suggesting that it plays a critical role in conidiation. The hypersensitivity of hat1Δ to Congo red demonstrates that disruption of hat1 impairs the integrity of cell wall. Overexpression of the wild‐type hat1 allele enhances conidiation by boosting the number of conidia. This is the first report on the role of a B‐type histone acetyltransferase in fungal secondary metabolism and cell wall integrity.